2010
DOI: 10.1016/j.rmed.2010.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of YKL-40, a chitinase-like protein, in serum and lung of patients with idiopathic pulmonary fibrosis

Abstract: These data suggest that YKL-40 is increased in the circulation and lungs of IPF patients, suggesting that this glycoprotein is associated with the pathophysiology of IPF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
87
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 26 publications
6
87
1
1
Order By: Relevance
“…Its roles in tissue remodeling and fibrosis have been investigated. A study in Japan (28) found that YKL-40 levels in serum and BALF were significantly higher in patients with IPF than in healthy controls. Serum levels of YKL-40 are significantly related to serum levels of KL-6.…”
Section: Ykl-40mentioning
confidence: 96%
“…Its roles in tissue remodeling and fibrosis have been investigated. A study in Japan (28) found that YKL-40 levels in serum and BALF were significantly higher in patients with IPF than in healthy controls. Serum levels of YKL-40 are significantly related to serum levels of KL-6.…”
Section: Ykl-40mentioning
confidence: 96%
“…54 Connective tissue growth factor, which was correlated negatively with 6-month change of FVC, 55 and YKL-40, which was significantly correlated positively with serum KL-6 and negatively with carbon monoxide diffusing capacity and Pa o 2 , 56 have also been investigated. Although all this research is promising, additional investigation, particularly into the development of a panel of biomarkers that have additive value to established clinical parameters, will be necessary to establish which biomarkers will be useful in clinical and research settings.…”
Section: Biomarkers Of Copdmentioning
confidence: 99%
“…Assessment of COPD exacerbations relies mostly on clinical 43,44,[58][59][60] ; MMP 5 matrix metalloproteinase 11,40,[49][50][51]53 ; MPIF-1 5 myeloid progenitor inhibitory factor-1 61 ; S100A12 53 ; SP 5 surfactant protein 10,[34][35][36][37]46,48,62,[58][59][60] ; TNF-a 5 tumor necrosis factor-a 10,26 ; TNFRSF1A 5 tumor necrosis factor receptor superfam ily, member 1A 51 ; VCAM-1 5 vascular cell adhesion moledule-1 53 ; YKL-40. 56 to identify clinical phenotypes such as rapid decliners and frequent exacerbators. Finally, we anticipate that biomarkers will be a part of a more stratifi ed and personalized approach to the classifi cation, prognostication, and treatment of the smoking-related parenchymal lung diseases.…”
Section: Biomarkers Of Copd and Ipf Exacerbationsmentioning
confidence: 99%
“…These results demonstrated that the force produced by ASM in response to a given stimulus is greater in a static environment than a dynamic environment. Oscillating strains at amplitude that is thought to prevail in vivo during breathing maneuvers also caused elongation of the contracted muscle (128,130,160). This later phenomenon is now referred to as force fluctuation-induced relengthening (FFIR).…”
Section: Stiffnessmentioning
confidence: 99%
“…The mechanisms underlying FFIR are not well understood but the length of the actin filaments seems to play a role (160). Collectively, these studies have shown that the force (66,84,85,128,186,198,242) and the stiffness (66,84,128,198) of ASM, as well as the length of the contracted ASM (128,130,160,186), are affected by length oscillations (66,84,85,128,130,160,186,198,242) or simply by an acute stretch (242). Considering these phenomena together, one can envision the following in vivo vicious cycle.…”
Section: Stiffnessmentioning
confidence: 99%